The Effects Of Electromagnetic Pulse (EMP) Attack ToHuman Life Reflected In William R. Forstchen's OneSecond After (2009) : Sociological Approach - Puspitasari, Noviana, Dr. M. Thoyibi, M.S, Mauly Halwat Hikmat, Ph. D (2014)
This Study is about the effects of electromagnetic pulse (EMP) attack to human life. The problem of this study is how the effects of electromagnetic pulse (EMP) attack to human life expressed in the One Second After novel. The objectives of this study are to identify the effects of electromagnetic pulse (EMP) attack to human life, and to reveal the relation between the novel and the author. The object of the study is One Second After by William R. Forstchen. It used sociological approach. This study belongs to qualitative research. In this method, there are two types of data source, namely primary and secondary data source. The primary data source is the novel and the secondary data is other material related to the study. Both data are collected through library research and analyzed by descriptive analysis. The result of the study shows the following conclusions. First, based on the structural analysis it is clear that in One Second After by William R. Forstchen the effects of electromagnetic pulse (EMP) attack can cause social disorder in society. Second, based on the sociological analysis, it is apparent that there is a strong relation between this novel and the social reality in America in early twenty first century.